1980
DOI: 10.1111/j.1751-0813.1980.tb02584.x
|View full text |Cite
|
Sign up to set email alerts
|

THE DISTRIBUTION OF MYCOBACTERIUM BOVIS IN QUEENSLAND CATTLE HERDS WITH OBSERVATIONS ON THE LABORATORY DIAGNOSIS OF TUBERCULOSIS

Abstract: Of 1,791 tissues submitted from 1975 to 1978 for histological examination for tuberculosis, 78.5% were classified as tuberculosis, 8.1% as club-forming granulomas, 3.3% as hydatid cysts, 3.4% as other granulomas and 2.4% as squamous cell carcinomas. Cultural examination of 2,682 tissues for mycobacteria yielded Mycobacterium bovis from 42.88%, other mycobacteria from 7.64% and 0.89% Rhodococcus (Corynebacterium) equi. Of 1,478 tissues on which both examinations were performed, culture and histology results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 8 publications
1
0
1
Order By: Relevance
“…The lesions were present more frequently in the respiratory tract (53.01%). This result reinforces previous publications that demonstrated that the respiratory pathway is the most important site of infection in cattle (CORNER et al, 1990;FREITAS;GUERRA;PANETTA, 2001;GRISI FILHO et al, 2011;ROGERS;DONALD;SCHULTZ, 1980;SOUSA et al, 2003;WHIPPLE;BOLIN;MILLER, 1996). The carcass was the area with the second highest distribution of lesions, with an occurrence rate of 20.23%.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The lesions were present more frequently in the respiratory tract (53.01%). This result reinforces previous publications that demonstrated that the respiratory pathway is the most important site of infection in cattle (CORNER et al, 1990;FREITAS;GUERRA;PANETTA, 2001;GRISI FILHO et al, 2011;ROGERS;DONALD;SCHULTZ, 1980;SOUSA et al, 2003;WHIPPLE;BOLIN;MILLER, 1996). The carcass was the area with the second highest distribution of lesions, with an occurrence rate of 20.23%.…”
Section: Resultssupporting
confidence: 90%
“…The head occupied was the fourth most common site of lesions among the five regions analyzed, with a frequency of 8.26%. This result differs from the results reported in other studies, which found that the head region was the second common site of bovine tuberculosis lesions (CORNER et al, 1990;FREITAS;GUERRA;PANETTA, 2001;GRISI et al, 2011;ROGERS;DONALD;SCHULTZ, 1980;SOUSA et al, 2003;WHIPPLE;BOLIN;MILLER, 1996). These differences are likely linked to individual immune responses.…”
Section: Resultscontrasting
confidence: 72%